Exposure to ionizing radiation affects the growth of ectomycorrhizal fungi and induces increased melanin production and increased capacities of reactive oxygen species scavenging enzymes. (February 2019) - Kothamasi, David; Wannijn, Jean; Van Hees, May; Nauts, Robin; Van Gompel, Axel; Vanhoudt, Nathalie; Vandenhove, Hildegarde
Abstract: Ectomycorrhizal (EM) fungi form symbioses with dominant tree families in boreal, temperate and tropical ecosystems and are important drivers of ecosystem function. EM fungal hyphae extend over a large area making them susceptible to enhanced radiation levels from naturally occurring or anthropogenically originating radioisotopes in the rhizosphere. In this study, the in-vitro effects of ionizing radiation on the growth and biomass of EM fungi Suillus luteus, S. bovinus and Rhizopogon luteolus were investigated. EM fungal cultures were exposed to gamma radiation from a 137 Cs source for 137 h in darkness at 21 °C at dose rates of 404, 108.5 and 54.9 mGy h −1 resulting in total absorbed doses of 55.21, 14.82 and 7.50 Gy respectively. Cultures grown in the dark at 21 °C but not exposed to the 137 Cs source served as the control. Our results show that EM fungi vary in their sensitivity to ionizing radiation. EM fungi used in this study produced melanin and reactive oxygen species scavenging enzymes such as catalase and superoxide dismutase as a response to ionizing radiation. Graphical abstract: Highlights: Ectomycorrhizal (EM) fungal strains used in this study form symbiotic interactions with terrestrial plants. Therefore the effects of radiation on these fungal groups can have ecosystem consequences. EM fungal cultures were exposed to gamma radiation doses of 55.21, 14.82 and 7.50 Gy respectively from a 137 Cs source for 137 h in darkness at 21 °C. Differences in biomass growth of exposed and unexposed cultures indicated the resistance or susceptibility of EM fungal strains to the varying doses of ionizing gamma radiation. The resistant strains responded to high doses of ionizing radiation with increased production of melanin and reactive oxygen species scavenging enzymes such as Catalase and Superoxide dismutase.